A novel efficient conference scheme for mobile communications. (6th August 2008) - Huang, Hui-Feng
A conference scheme enables a group of people to establish a common secret key to hold a secure conference. Recently, technological advances have allowed all conferees to hold a mobile conference via wireless communication. However, wireless communications are more susceptible to eavesdropping and unauthorised access than conversations via wires. Therefore, it is crucial to ensure confidentially and authenticity in mobile teleconferencing. Based on the Elliptic Curve Cryptography, this article proposes a new efficient conference scheme, which allows a participant to join or quit a teleconference dynamically. No trusted centre and no interactive protocol among participants are required to construct the common conference key for each session. It can save on communication overhead.